(untitled) (Kronika Bydgoska, 2013)
As regards music, the 1960’s in Bydgoszcz had the same features that characterised entire Poland at that time. Plenty of local big beat bands were established in spite of the lack of professional equipment, such as guitars and amplifiers, on the market. With the passage of time the situation started to change when, for example, the Bydgoszcz accordion factory started the production of guitars. Music bands mainly co-operated or were active within Company Culture Centres and Youth Culture Centres, where they could use sound-amplifying equipment. The authorities of the Polish People’s Republic and press did not treat big beat seriously, and their attitude towards jazz music in the initial stage was similar, though in the wake of political thaw this genre started to be treated with more respect. However, the jazz stage was less propagated in Bydgoszcz, though the Traditional Jazz Group and bassist Jacek Bednarek were successful. Big beat bands had lots of opportunities to perform for Bydgoszcz audiences, mainly thanks to Gitariada concerts. There were also several jazz clubs. The company Estrada Bydgoska (Bydgoszcz Stage) operated separately. The most important big beat and pop artists performed in Bydgoszcz in the 1960’s. Additionally, several concerts of foreign bands were held, though these were rather inferior groups.